STUDI SISTEM TRANSPORTASI DI KAWASAN STASIUN BEKASI DENGAN KONSEP TRANSIT ORIENTED DEVELOPMENT (TOD) - Angeline Gracia Samudra; Liong Ju Tjung (Jurnal Sains, Teknologi, Urban, Perancangan, Arsitektur (Stupa), 2022)
The problem of congestion can be overcome by improving the integration of macro transportation systems and realized by the concept of Transit Oriented Development (TOD). Directions fot the development of TOD already exist in various regions in Indonesia, one of which is in the Bekasi Station area, located in Bekasi City, West Java, which is stated in Presidential Regulation of the Republic of Indonesia No. 55 of 2018 concerning the Greater Jakarta Transportation Master Plan for 2018-2029. The Bekasi Station area is planned to be a city-scale transit node with the main mode of transportation, namely trains. The poor condition of the transportation system in the Bekasi Station area is a direct factor for the development of TOD in this area. This can be seen from the traffic jams in the Bekasi Station area. Congestion is also common every day, especially during peak hours in the afternoon from 17.00 to 20.00 WIB. The Bekasi Stasion area has the potential to be developed with the TOD concept because in this area there is still an empty area of 24.33 hectares that can be developed (survey results, 2022). Therefore, this study aims to analyze the condition of the regional transportation system which consists of a system of activities, a network system and a movement, and to find out the development strategy based on the TOD concept in the Bekasi Station area. The analysis in this study uses qualitative and quantitative methods. The results of this study are a strategy to fix transportation system problems in the Bekasi Station area with the concept of Transit Oriented Development (TOD). Keywords: Integration, Transportation System, Transit Oriented Development Abstrak Persoalan kemacetan dapat diatasi dengan memperbaiki integrasi sistem transportasi makro dan diwujudkan dengan konsep Transit Oriented Development (TOD). Arahan pengembangan TOD sudah terdapat di berbagai wilayah di Indonesia, salah satunya ialah di kawasan Stasiun Bekasi yang terletak di Kota Bekasi, Jawa Barat yang tercantum dalam Peraturan Presiden Republik Indonesia No. 55 Tahun 2018 tentang Rencana Induk Transportasi Jabodetabek Tahun 2018-2029. Kawasan Stasiun Bekasi direncanakan menjadi simpul transit berskala kota dengan moda transportasi utama yaitu kereta api. Kondisi sistem transportasi yang buruk di kawasan Stasiun Bekasi menjadi faktor arahan pengembangan TOD di kawasan ini. Hal tersebut dapat terlihat dari masih ditemukannya kemacetan pada kawasan Stasiun Bekasi. Kemacetan juga biasa terjadi setiap hari terutama pada  peak hour pada sore pukul 17.00-20.00 WIB. Kawasan Stasiun Bekasi juga memiliki potensi untuk dikembangkan dengan konsep TOD karena dalam kawasan ini masih terdapat lahan kosong seluas 24,33 hektar yang dapat dikembangkan (hasil survei, 2022). Oleh karena itu, penelitian ini bertujuan untuk mengetahui kondisi sistem transportasi kawasan yang terdiri atas sistem kegiatan, sistem jaringan dan pergerakan, dan untuk mengetahui strategi pengembangan berdasarkan konsep TOD di Kawasan Stasiun Bekasi. Analisis dalam penelitian ini menggunakan metode kualitatif dan kuantitatif. Hasil penelitian ini berupa strategi untuk membenahi permasalahan sistem transportasi di kawasan Stasiun Bekasi dengan konsep Transit Oriented Development (TOD).